The importance of paraoxonase 1 activity, nitric oxide and lipid peroxidation in hepatosteatosis - Atamer, A.; Bilici, A.; Yenice, N.; Selek, S.; Ilhan, N.; Atamer, Y. (Sage Publications Ltd, 2008)
This study evaluated the changes in oxidative status in hepatosteatosis patients in terms of lipid peroxidation, nitric oxide (NO) and paraoxonase I (PON1) activity. A total of 49 patients with hepatosteatosis (29 males and 20 females, mean age 47.2 +/- 3.6 years) and 25 healthy subjects (IS males and 10 females, mean age 46.1 +/- 3.2 years) were enrolled in the study. Serum PON1 was measured spectrophotometrically, malondialdehyde (MDA), an end-product of lipid peroxidation, was determined using the thiobarbituric acid method., and NO was assessed using the Griess reaction. Lipid and other biochemical parameters were determined by routine laboratory methods. PON1 activity and NO levels were significantly decreased and MDA levels significantly increased in hepatosteatosis patients compared with healthy subjects. PON1 activity was correlated with MDA level and NO level. In conclusion, oxidative stress seems significantly to suppress PON1 synthesis in hepatosteatosis patients. In addition, oxidative stress and oxidant-antioxidant imbalance may be part of the cytotoxic mechanisms leading to liver cell injury.
Keywords: hepatosteatosis; paraoxonase; nitric acid; lipid peroxidation; lipoprotein